E-commerce project implementation. - Lim, Ching San. (2008)
This paper seeks to provide a comprehensive understanding of what should be done from the conclusion of planning to the implementation of an e-commerce project in the retail industry. Our research was based on a model consisting of five sub-parts; project objectives, project nature, project methodology, human issues and infrastructure.